The effect of body roll on hand speed and hand path in front crawl swimming - A simulation study - Payton, C. J.; Hay, J. G.; Mullineaux, D. R. (Journal of Applied Biomechanics, 1997)
The aim of this study was to predict the effect of body roll on hand speed and hand path during the pull phase in front crawl swimming. An earlier three-segment model (Hay, Liu, & Andrews, 1993) was developed to enable the hand to move out of the plane through the shoulder parallel to the sagittal plane of the rotating trunk. Elbow flexion, shoulder abduction, and body roll angular velocities were modeled as sine or cosine functions. For a given elbow flexion, an increase in maximum body roll from 45° to 60° produced a marked increase in medial hand motion. For a given body roll, an increase in maximum elbow flexion from 60° to 90° increased medial hand motion and reduced downward hand motion. An increase in body roll increased hand speed in the plane perpendicular to the swimming direction, thus increasing the potential of the hand to develop propulsive lift forces.